Eksistensi dan Ancaman Usaha Pegaraman di Gampong Cebrek Kabupaten Pidie - Ibnu Phonna Nurdin; Dara Fatia; Cut Lusi Chairunnisak (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
Barriers in salt farming endeavors are constantly encountered by salt farming communities, thereby impacting the future sustainability of salt production. This article aims to describe the sustainability threats posed by traditional salt farming activities in Gampong Cebrek, Simpang Tiga Subdistrict, Pidie Regency. The article presents findings from a qualitative field research conducted using observational data and in-depth interviews with selected traditional salt farmers employing purposive sampling technique. The study reveals that the existence of traditional salt farming activities in Gampong Cebrek, Pidie Regency, is confronted with several issues that could potentially jeopardize their future existence. Firstly, the regeneration process of salt farmers is not progressing effectively. Secondly, the declining participation and capabilities of salt farmers due to their advanced age. Thirdly, government policies have led to a decrease in production and distribution of salt. Lastly, the conversion of agricultural land into residential areas has occurred. Abstrak Hambatan dalam usaha pegaraman selalu terjadi pada komunitas petani garam yang berdampak pada keberlanjutan usaha garam di masa mendatang. Artikel ini bertujuan untuk mendeskripsikan tentang ancaman keberlanjutan dari aktivitas pertanian garam tradisional di Gampong Cebrek, Kecamatan Simpang tiga, Kabupaten Pidie. Artikel ini merupakan hasil penelitian lapangan menggunakan metode kualitatif. Data diperoleh dari hasil observasi dan wawancara mendalam kepada petani garam tradisional yang dipilih menggunakan teknik purposive. Kajian ini menunjukkan bahwa eksistensi aktivitas pertanian garam tradisional di Gampong Cebrek Kabupaten Pidie dihadapkan pada beberapa persoalan yang kemudian dapat mengancam eksistensi mereka di masa mendatang. Pertama, proses regenerasi pertani garam yang tidak berjalan dengan baik. Kedua, partisipasi dan kemampuan petani garam yang semakin menurun karena telah memasuki usia senja. Ketiga, kebijakan pemerintah yang berdampak pada menurunnya aktivitas produksi dan distribusi garam. Keempat, terjadinya alih fungsi lahan pertanian menjadi lahan pemukiman.